1993
DOI: 10.1152/ajprenal.1993.264.3.f548
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for existence of two distinct bradykinin receptors on rat mesangial cells

Abstract: We investigated the possible presence of bradykinin (BK) B1 receptor on rat mesangial cells (MC) by binding studies and by the effect of the B1 agonist des-Arg9-BK on intracellular calcium concentration ([Ca2+]i) and DNA synthesis in comparison with the effects of BK. Binding studies demonstrated specific, saturable binding for des-Arg9-[3H]BK inhibited by B1 but not by B2 antagonists. Scatchard analysis revealed a single class of B1 binding site with a maximum density of 15 fmol/mg protein and an affinity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
49
0
8

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 0 publications
9
49
0
8
Order By: Relevance
“…These values are similar to that obtained from calcium studies of the B1 receptor in rat mesangial cells (560 nM; Bascands et al, 1993) and are in the same concentration-range as those observed in the 'classic' B1 receptor system, contractile responses of the rabbit aorta, where the EC5o was found to be 50 nM (Regoli et al, 1981).…”
Section: Image Analysissupporting
confidence: 86%
“…These values are similar to that obtained from calcium studies of the B1 receptor in rat mesangial cells (560 nM; Bascands et al, 1993) and are in the same concentration-range as those observed in the 'classic' B1 receptor system, contractile responses of the rabbit aorta, where the EC5o was found to be 50 nM (Regoli et al, 1981).…”
Section: Image Analysissupporting
confidence: 86%
“…Glomeruli were isolated as routinely performed in the laboratory by graded sieving (6). Briefly, rats were anesthetized intraperitoneally with 65 mg/kg pentobarbital sodium (Sanofi, Montpellier, France) and killed by exsanguination, and the kidneys were quickly removed.…”
Section: Ex Vivo Experimentsmentioning
confidence: 99%
“…Whereas the initial studies conducted only with quiescent cells demonstrated mainly mitogenic effects (6,20), more recent studies by several groups report inhibitions of both cell proliferation and ERK1/2 phosphorylation by BK. Dixon and Dennis (15) evidenced an inhibition of mitogenesis by BK in arterial smooth muscle cells stimulated with PDGF-AB.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The kidney contains various components of KKS, and bradykinin (BK), the most important bioactive peptide of KKS, is the final effector exerting the effects described above. The presence of BK receptors at the surface of mesangial cells has been confirmed, and the B2 receptor of BK shows particularly high expression (Bascands et al, 1993). Glomerulosclerosis is a common developmental process of chronic kidney disease, which mainly acts to increase MCP and ECM secretion.…”
Section: Introductionmentioning
confidence: 88%